X^2-4X+Y^2+6Y+13=0,求2X-Y的值.
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 06:13:44
X^2-4X+Y^2+6Y+13=0,求2X-Y的值.X^2-4X+Y^2+6Y+13=0,求2X-Y的值.X^2-4X+Y^2+6Y+13=0,求2X-Y的值.X^2-4X+Y^2+6Y+13=(X
X^2-4X+Y^2+6Y+13=0,求2X-Y的值.
X^2-4X+Y^2+6Y+13=0,求2X-Y的值.
X^2-4X+Y^2+6Y+13=0,求2X-Y的值.
X^2-4X+Y^2+6Y+13=(X-2)^2+(Y+3)^2=0
X=2,Y=-3
2X-Y=7
X^2-4X+Y^2+6Y+13=0
(x-2)^2+(y+3)^2=0
x-2=0 x=2
y+3=0 y= -3
2x-y = 2*2- (-3) =7
已知x^2+y^2+13-4x+6y=0,求(2x-y)^2-2(2x-y)(x+2y)+(x+2y)^2
已知:x^2+y^2+4x-6y+13=0,求x^y值.
x^2+y^2+4x-6y+13=0,求x^y的值
x^2-4x+y^2-6y+13=0求x,y的值
若x^2+y^2-6x+4y+13=0 求x+y
因式分解 若 x^2+4x+y^2-6y+13=0 求y^x
x^2+y^2+6x-4y+13=0求x,y,x^2-y^2的值
化简求值:已知x、y满足:x^2+y^2-4x+6y+13=0 求代数式 的值.(3x+y)^2-3(3x-y)(x+y)-(x-3y)(x+3y)急用!
已知x²+y²-6x+4y+13=0,求(2x-y)²-2(2x-y)(x+2y)+(x+2y)²已知x²+y²-6x+4y+13=0,求(2x-y)²-2(2x-y)(x+2y)+(x+2y)²
已知x、y满足x2+y2-4x+6y+13=0 求代数式(3x+y)2-3(3x-y)(x+y)-(x-3y)(x+3y)已知x、y满足x^2+y^2-4x+6y+13=0 求代数式(3x+y)^2-3(3x-y)(x+y)-(x-3y)(x+3y)的值
已知x*x-4xy+4y*y=0 求[2x(x+y)-y(x+y)]/(4x*x-4xy+y*y)的值?
已知x.x+y.y+8x+6y+25=0,求代数式(x.x-4y.y)/(x.x+4xy+4y.y)-x/(x+2y)的值
x*x+2x-y*y+6y-8=0,x+y不等于2,求x-y的值
已知X*X+Y*Y+6X-8Y+25=0 求(Y/X)+(X/Y)-2=?
x^2+y^2+13=6x-4y求x^y的值
x^2+y^2+13=6x-4y,求x^y的值
x^2+y^2+13=6x-4y求x^y的值
已知:4x^2+y^2-4x-6y+10=0,求y/x-x/y的值